2006
DOI: 10.1002/app.23589
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crosslinking on the mechanical properties of polylactic acid/polycaprolactone blends

Abstract: ABSTRACT:The improvement of the brittle behavior of Polylactic acid (PLA) resin was studied by blending it with Polycaprolactone (PCL) resin. These materials were fabricated into the compressed films and injection moldings. The values of tensile modulus and strength were appropriate, judging from the rule of mixtures. However, the ultimate tensile strain was very small. Dicumyl peroxide (DCP) was added to this blend system to improve its ultimate tensile strain. It was found that the value of ultimate tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
235
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(258 citation statements)
references
References 10 publications
13
235
2
2
Order By: Relevance
“…Block-copolymers can be produced by reactive extrusion of the polymers with peroxides, as done for PLA/PBAT, PLA/PBS and PLA/PCL blends. [72][73][74] To alter the live-time of generated radicals and therefore alter the possibility of diffusion, so-called 'vector-fluids' were used. 66 Additionally, 'surfactants' based on ambipolar molecules with a miscible polar component were used.…”
Section: Part IImentioning
confidence: 99%
“…Block-copolymers can be produced by reactive extrusion of the polymers with peroxides, as done for PLA/PBAT, PLA/PBS and PLA/PCL blends. [72][73][74] To alter the live-time of generated radicals and therefore alter the possibility of diffusion, so-called 'vector-fluids' were used. 66 Additionally, 'surfactants' based on ambipolar molecules with a miscible polar component were used.…”
Section: Part IImentioning
confidence: 99%
“…Morphological study and rheological properties indicated that GMA acts as a monomeric plasticizer and a reactive agent at the interface between PLA and PCL phases. Semba and coworkers [95,96] determined the effect of DCP cross-linking on the structure and mechanical properties of PLA/PCL blends. It was found that the diameter of the PCL particles decreased with higher content of DCP during in-situ compatibilization, which results in mechanical properties improvement for the PLA/PCL blend.…”
Section: Aliphatic Polyesters Blendsmentioning
confidence: 99%
“…The results shown in Figure 1A indicate that the addition of 5% (w/w) PLLA reduced the tensile strength and elongation at break by 32% and 85% respectively. This concentration level was chosen as it was in accordance with that used in the literature (commonly 20% (w/w)) (Maglio et al, 2003;Semba et al, 2006).…”
Section: Tensile Propertiesmentioning
confidence: 99%